The Anaerobic Power of Women who have Undergone Physical Training - Cezary Michalski; Michał Zych; Wiesław Pięta; Karol Pilis; Wiesław Pilis; Anna Pilis; Krzysztof Stec; Joanna Rodziewicz-Gruhn (Lesya Ukrainka Volyn National University, 2017)
Introduction. Anaerobic power is an important factor determining the physical performance in various kinds of sports. Therefore, the aim of this paper is to present women's anaerobic power in soccer players (SP), table tennis players (TT) and weightlifters (WL). Methods. This study involved 3 groups of professional athletes women: 15 SP, 12 TT and 12 WL, which are of a similar age and sports' level. Anaerobic power in all athletes was recorded during 30-second Wingate test, with resistance set at 0,075 kp x kg (-1). Results. Relatively expressed total external work (TW), maximal power output (Pmax) and the fatigue index (FI) of tested athletes were similar. Mean power (Pmean) was different among the treatment groups (F=12,445; p<0,001), while in TT group these values were significantly lower than in SP and in WL athletes. Somatic variables in 3 groups of tested athletes have not changed. Conclusions. Type of practiced sport has an impact on the size of anaerobic power. Several years of sports training in table tennis has not changed the anaerobic potential of surveyed women while specific training in soccer and weightlifting increased only Pmean.